Dental Caries Vaccines –An Emerging Viable Treatment for Modern Dentists - Sudipta Sahu; Kajal Kiran Sahoo; Debashruti Naik; Sharmistha Mohanty (Institute of Medico-legal Publications Pvt Ltd, 2021)
Dental caries is an irreversible microbial disease of the calcified tissues of the teeth. It is a bacterial driven,generally chronic, site-specific, the multifunctional dynamic disease process that results when the PH dropresults in net mineral loss over time. It is one of the most prevalent diseases affecting mankind. Cariogenicbacteria enter the dental biofilm early in life and subsequently invade the host tissue during favourableenvironment condition, to cause the disease. Many studies and researches show that this disease processcan be interrupted. This article will give a clear idea of the method by which the host defence system can bearoused to combat dental caries caused by the crucial antigen related to Streptococcus mutans. Analyzingthe fact that more effective public dental health care measures are needed to combat this dental caries, thisarticle critically evaluates the recent signs of progress in the development of mucosal adjuvants, deliverysystems for the dental vaccine, and also limitations of caries immunization.